Emerging adulthood and Type 1 diabetes: insights from the DAWN2 Study. Issue 2 (14th January 2018) - Vallis, M.; Willaing, I.; Holt, R. I. G.
What's new?: Compared with individuals with Type 1 diabetes aged >30 years, emerging adults reported better overall quality of life but greater diabetes distress and lower levels of self‐management. Diabetes education appears to be as valuable to emerging adults with Type 1 diabetes as it is to adults aged >30 years. These results support the recommendation of assessing diabetes distress in emerging adults with Type 1 diabetes. Assessing overall quality of life is likely to miss important psychological issues, specific to the experience of Type 1 diabetes. Abstract: Aims: To compare clinical, psychological, education and social variables in emerging adults (aged 18–30 years) with Type 1 diabetes with their adult counterparts aged >30 years. Methods: A single assessment multinational sample was surveyed as part of the larger second Diabetes Attitudes, Wishes and Needs (DAWN2) study. Participants completed a series of surveys incorporating demographic as well as clinical questions (comorbidities, hypoglycaemia) and validated self‐report scales concerning psychosocial (health impact, quality of life, beliefs and attitudes, self‐management behaviours, healthcare experience and family support) and diabetes education factors. Results: Emerging adults differed from adults aged >30 years with regard to a number of psychosocial variables. Emerging adults reported better overall quality of life, social support and support from their healthcare team compared with adults aged >30 years of age; however, emerging adults experienced greater diabetes‐specific distress and were less engaged in self‐management. Diabetes education was related to a number of indicators, while experience of discrimination was harmful, but these impacts did not differ between emerging adults and adults aged >30 years. An analysis of geographical regions suggested that emerging adults in North America and Europe had better well‐being than older adults, while the opposite was observed in Asia. Conclusions: Emerging adults, particularly those in the later phase (ages 25–30 years) are especially at risk in terms of diabetes‐specific distress. There is a need for novel interventions to meet the needs of these vulnerable emerging adults more effectively.